Scaling up Hacienda San Jose sustainable ranch model and securing private sector finance - Arango, Jacobo; Rubio, N.M.; Costa, C. Jr.; Bastidas, M.; Perez, J.; Rogriguez, L.; Cardoso, Juan Andrés (CGIAR System Organization, 2024)
In Colombia, the Initiative on Livestock and Climate benefited from extensive work previously conducted by implementing partner Alliance Bioversity International– CIAT. Their research into tropical grasses demonstrated significant potential as a technology for reducing greenhouse gas emissions while enhancing livestock productivity. Action research based on this work has been undertaken by Initiative partner scientists using the Hacienda San Jose (HSJ) ranch as a study area. Alliance researchers pursued three pathways: (1) developing and scaling climate‐smart livestock practices, (2) building resilience of low-emission livestock production systems, and (3) mobilizing investments to drive sustainable livestock systems. Evidence of these outcomes is substantiated through a synthesis of the results, innovations and partnerships.